Management of shariah non-compliance risk in Maybank Islamic Berhad / Muhammad Reza Amin Reza Adnan - Reza Adnan, Muhammad Reza Amin (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
The objective of this paper is to study the management of shariah noncompliance risk associated with Maybank Islamic Berhad. Having a precise definition of shariah non-compliance risks is highly necessary for the purpose of developing a comprehensive risk management framework for an Islamic financial system. This study is conducted through a literature review on regulatory provisions and existing academic journals and thesis on Islamic risk management. This paper provides an in-depth discussion on the guidelines in managing shariah non-compliance and the factors that lead to shariah noncompliance risk and also the strategies that used by Maybank Islamic Berhad in order to counter this type of risk. These elements of risk were identified as that emerging from the entire process of developing an Islamic financial product, starting from the structuring stage until the execution of the product in the market hence cause severe both financial and non-financial costs to Maybank Islamic Berhad. This research may have some implications to the Islamic finance industry in Malaysia, which would be useful for further empirical research in this area.